IMPLICATIONS OF NON-EXCLUSIVE CHOICE OF FORUM CLAUSES IN DETERMINING THE COMPETENT DISPUTE RESOLUTION FORUM IN INDONESIA - Vickya, Alvansa; Allagan, Tiurma M.P. (Indonesia Law Review, 2022)
This research aims to analyze the implications of a non-exclusive choice of forum clause in determining the competent dispute resolution forum in Indonesia based on theories related to Private International Law, International Contract Law, and International Civil Procedure Law. Based on the results of this research, the implications of the non-exclusive choice of forum clause in determining the competent dispute resolution forum in Indonesia have not been fully regulated by Indonesian laws and regulations. This can be seen from the use of the doctrines of forum non conveniens, lis pendens, and res judicata, the three of which are still not contained in the laws and regulations in Indonesia, even though there are already doctrines implied in Article 118 of HIR, namely the basis of presence and the principle of effectiveness. This shows that there is no legal certainty regarding a dispute in which the parties have a non-exclusive choice of forum. Therefore, it would be better if Indonesia had a written law about Private International Law and ratified the Hague Choice of Court Convention 2005 to provide certainty, justice, and legal benefits for every party who will act in the civil and commercial law field, especially in disputes arising from international contracts in which there is a non-exclusive choice of forum.